Empirical Determination of Losses in an Optical Fibre Link - Onaifo, F.; Alao, P. O.; Oyedeji, A. O.; Olasukanmi, O. G.; Temidayo, A. S.; Lawal, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper analyses the characteristics of signal loss in optical fibre link with splicing loss forming part of the total loss with the loss measurement carried out with the aid of Optical Time Domain Reflector.An Optical Time Domain Reflectometer (OTDR) is made up of a detector and a laser. Light signals are sent into the fibre using a laser and a demodulator or a detector on the other end to receive the signals. The received signal is displayed on a graph. The transmitted signal is a pulse with a given amount of energy. A clock determines the time duration of the signal. This paper explains the splicing using Optical Time Domain Reflectometer. These losses in an optical fibre cable arise from spliced points and joints with either connectors or any other passive fibre optic device. The study shows that losses along optical fibre arise from the splice joint, connector joint and along the fibre length as attenuation loss. These losses were obtained from readings of the optical time domain reflectometer. The study also shows that the combined splicing and connector loss is higher than attenuation loss. Here, splicing and connector loss contributes 75% of the total losses while attenuation losses account for the remaining 25%. An attempt should, therefore, be made to reduce splices in order to minimize losses when using optical fibre cabling.